The antiquity of Jaffna Fort: new evidence from post-disaster archaeological investigations in northern Sri Lanka. (10th April 2019) - Davis, Christopher; Coningham, Robin; Gunawardhana, Prishanta; Pushparatnam, P.; Schmidt, Armin; Manuel, Mark
Abstract: Abstract : Post-disaster archaeological investigations at Jaffna Fort have revealed material demonstrating pre-colonial contact, shedding new light on the importance of the site in Indian Ocean trade and communications networks before European occupation.